Characteristics of Auditors and the Detection of Fraud in Financial Statements - Goleyjani, Mehrdad; Giyah khah, setayesh; Pourfeizollah, Rasoul (International Journal of Business Management and Entrepreneurship, 2023)
This study aims to investigate how certain characteristics of auditors are linked to their ability to identify fraud in financial statements. The research involved selecting a sample size of 110 companies from 2013 to 2021 using a systematic method. A descriptive survey was used to gather data, and a regression model was estimated using panel data to analyze multiple regressions. The results of the study indicate that there is a strong association between audit tenure, auditor independence, industry expertise, and the size of the audit firm in the identification of fraud. Audit turnover was found to have a significant negative impact on fraud detection. However, there was no significant association between audit report delays and fraud detection.